DESIGN OF A COMPRESSION STRUCTURE WITH INNER RIBS USING FORCE DENSITY METHOD & TOPOLOGICAL MAPPING - Fernández Ruiz, Manuel Alejandro; Gil-Martin, Luisa Maria (Journal of Applied Engineering Science, 2016)
Compression-only structures can be modelled as pin-jointed networks with all the members in compression. The final shape of the network can be computed using the Force Density Method (FDM) together with Topological Mapping (TM), introducing the self-weight iteratively until the equilibrium is found. One of the input parameters of FDM is the force-length ratio q of each member of the network. Members with a high q carry a higher level of loads, working as ribs of the structure. The designer defines the proper distribution of the ribs in the network, resulting in aesthetical final shapes. Here, a two-storey compression structure with inner ribs has been designed using TM-FDM.